Effect of hydrochar from acid hydrolysis on anaerobic digestion of chicken manure. Issue 5 (October 2022) - Hurst, G.; Ruiz-Lopez, S.; Rivett, D.; Tedesco, S.
Abstract: Acid hydrolysis is a key process for the production of platform chemicals from biomass, however solid residues by-products can amount to 50 wt% of the starting biomass material. In this study, solid residues from the production of biofuel precursor levulinic acid were generated via microwave-assisted acid hydrolysis of Miscanthus x Giganteus and investigated for the supplementation of anaerobic reactors digesting Chicken Manure. The addition of the solid residues increased the methane yields by up to 14.1%, depending on the additive concentration levels, 2–10 g/L. A mild ammonium related inhibition was observed during the fermentation trials, which was mitigated by the solid residue additive. An experimental optimum of concentration 6 g/L residue was found which corresponded with a 20% decrease in ammonium concentrations and increased microbial diversity, where phyla Bacteroidetes and Firmicutes were the most prevalent, whilst the relative abundance of Archaea (Euryarchaeota) decreased without negative effects on methane production. The effects of acid catalysis conditions on solid residue properties and methane yields from chicken manure were evaluated. All solids residue investigated exhibited ammonium absorption and improved microbial diversity during anaerobic digestion. The integration of anaerobic digestion downstream second generation biorefineries is a promising green waste disposal method for solid by-products from thermo-catalytic processes. Graphical Abstract: ga1 Highlights: Residual solids from microwave production of levulinic acid exhibits hydrochar properties. Solid residue addition increases methane yields from chicken manure digestion by up to 14%. Solid residue addition improves microbial diversity and reduces ammonium concentrations. Inhibition of methane production was observed from residues at harsher catalysis conditions.